INVESTIGATION OF PERCEPTUAL LEARNING STYLE OF CFL LEARNERS: THE CASE OF MANDARIN CLASSES AT UNIVERSITI TUN HUSSEIN ONN MALAYSIA(UTHM) - CHENG, YEOH LI (Human Sustainability Procedia, 2018)
Learning style is a way which an individual prefers to use in the process of acquiring knowledge and skills. Studies on learning style can give educators new directions for making changesin teachingmethodsto improve students’ performance. This study was conducted to identify the predominant learning style preferences of Chinese as foreign language (CFL) learners atUniversiti Tun Hussein Onn Malaysia (UTHM). The relationshipbetween learning style and individual attributes such as gender and faculty was also explored. The Perceptual Learning Style Preference Questionnaire (PLSPQ) developed by Joy M. Reid was usedand administered to 148 students. The data were analysed using percentage analysis. The results indicated that primary and secondary learning style of the students were kinesthetic and group learning.